High-transparency degradable thin film material as well as preparation method and application thereof

By adding a specific amount of antioxidants, melt compatibility agents and modifiers to the preparation of polyetric acid thin membrane materials, and control the cooling rate, the problem of high light transmission and brittleness of PGA materials is solved, and the high transparency is achieved. , Low mist and excellent stretching toughness have expanded its application in the field of packaging.

CN119350671AActive Publication Date: 2025-01-24CHINA ENERGY INVESTMENT CORP LTD +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202310908107.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-24
Publication Date
2025-01-24
Estimated Expiration
2043-07-24

AI Technical Summary

Technical Problem

The polyglycolic acid (PGA) material itself has poor light transmittance (light transmittance less than 70%, haze greater than 80%) and high brittleness, which limits its wide application in the packaging field.

Method used

By combining polyglycolic acid, antioxidants, melt compatibilizers and modifier terephthalamide in specific amounts, and controlling the cooling rate ≥150°C/min during the preparation of film materials, polyethylene glycol can be significantly improved. Transparency and mechanical properties of acid film materials.

Benefits of technology

The light transmittance of polyethylene membrane materials was achieved than 87 %, and the fog is less than 10 %, which greatly improved its stretching toughness and broaden its application in the packaging field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004354153340000051
    Figure BDA0004354153340000051
  • Figure BDA0004354153340000061
    Figure BDA0004354153340000061
Patent Text Reader

Abstract

The invention discloses a high-transparency degradable thin film material as well as a preparation method and application thereof. By adopting the method disclosed by the invention to prepare the thin film material based on the PGA, the thin film material with higher transparency and lower haze can be obtained, and the thin film material has improved tensile toughness at the same time. The preparation method comprises the following steps: uniformly mixing raw materials, then carrying out melt blending extrusion and granulation in a twin-screw extruder, carrying out film pressing on the obtained particles, then cooling to obtain a film, and controlling the cooling rate to be more than or equal to 150 DEG C / min, preferably 150-300 DEG C / min during cooling, the raw materials comprise the following components in parts by weight: 90-98 parts of polyglycolic acid, 0.3-2 parts of an antioxidant, 0.5-3 parts of a melt compatilizer and 1-5 parts of a modifier; the modifier is selected from terephthalamide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer materials and relates to a highly transparent degradable film material and a preparation method and application thereof. Background Art

[0002] In recent years, disposable plastic products have brought a heavy burden to the ecological environment. Since the implementation of the "Plastic Ban", degradable polymer materials have received widespread attention. Among them, polyglycolic acid (PGA) is an aliphatic polyester polymer material with a simple chemical structure, a completely decomposable polyester structure, and the fastest degradation rate. PGA has good biodegradability, biocompatibility, gas barrier properties, and excellent mechanical strength. However, due to the shortcomings of PGA's high brittleness and poor transparency, its wide application in the packaging field is severely limited. Therefore, it is very important to improve the light transmittance and toughness of PGA.

[0003] CN108003581B discloses a polylactic acid composite material and its application. The composition of the polylactic acid composite material includes polylactic acid, talcum powder and plasticizer. When the polydispersity index of polylactic acid is in the range of 1.55-2.02, by adding talcum powder with a particle size of 1-2.6μm and a plasticizer with a relative molecular weight of 180-670, a polylactic acid composite material with a transmittance of ≥80% and a haze of ≤40% can be obtained. The key technology of this patent involves the control of the dispersion index, and the dispersion of dispersed particles is difficult to monitor in real time in actual operation. In addition, the transmittance of the material prepared by this patent is still low and the haze is still large.

[0004] CN111440425A discloses a method for producing highly transparent polylactic acid, which comprises the steps of high-temperature baking and boiling of plant fibers to form transparent blocks, high-temperature mixing and hot pressing to form transparent starch blocks, and then blending with polylactic acid to obtain highly transparent polylactic acid materials. The process steps of this method are relatively complicated, and no corresponding data is mentioned for the transparency of the obtained material.

[0005] Currently, there are few reports on the use of PGA to prepare biodegradable film materials with high light transmittance and low haze. Summary of the invention

[0006] In view of the shortcomings of the current polyglycolic acid (PGA) material itself, such as poor light transmittance (transmittance less than 70%, haze greater than 80%) and high brittleness, the method of the present invention is used to prepare a thin film material based on PGA, so that a thin film material with higher transparency and lower haze can be obtained, and the thin film material also has improved tensile toughness.

[0007] To achieve the purpose, the present invention provides the following technical solutions:

[0008] In one aspect, the present invention provides a method for preparing a highly transparent degradable film material, comprising the following steps:

[0009] The raw materials are mixed uniformly, and then melt-blended and extruded in a twin-screw extruder to form pellets, and then film pressed and cooled to obtain a film, and during the cooling, the cooling rate is controlled to be ≥150°C / min, preferably 150-300°C / min;

[0010] The raw materials include the following components: 90-98 parts by weight of polyglycolic acid, 0.3-2 parts by weight of antioxidant, 0.5-3 parts by weight of melt compatibilizer, and 1-5 parts by weight of modifier;

[0011] The modifier is terephthalamide.

[0012] The present invention prepares a film material by combining polyglycolic acid, an antioxidant, a melt compatibilizer and a specific modifier in the above-mentioned amounts, and controls the cooling rate during the cooling process to be ≥150°C / min (preferably 150-300°C / min), which can significantly improve the transparency of the polyglycolic acid film material, significantly reduce its haze, and have good mechanical properties.

[0013] In some embodiments, the weight average molecular weight of the polyglycolic acid is ≥50,000, preferably 50,000-250,000; the melt index of the polyglycolic acid at 240° C. and 2.16 kg load is 5-120 g / 10 min, preferably 10-50 g / 10 min;

[0014] The polyglycolic acid may be a homopolymer of glycolic acid or a copolymer of glycolic acid.

[0015] In some preferred embodiments, the antioxidant is selected from one or more of phosphite antioxidants and hindered phenol antioxidants; preferably, the antioxidant is a combination of a phosphite antioxidant and a hindered phenol antioxidant, and preferably the mass ratio of the two is 0.8-1.2:1; using the preferred antioxidant is conducive to obtaining a film material with better resistance to thermal oxidative aging.

[0016] Further preferably, the phosphite antioxidant is selected from one or more of antioxidant 168, antioxidant 626 and antioxidant 9228; the hindered phenol antioxidant is selected from one or more of antioxidant 1010 and antioxidant 1330.

[0017] In some preferred embodiments, the melt compatibilizer is selected from one or more of epoxy compounds and polyisocyanate compounds. The use of a preferred compatibilizer is conducive to enhancing melt strength, improving the compatibility of each component, and obtaining a product with better film-forming properties.

[0018] In some preferred embodiments, the epoxy compound is selected from copolymers containing glycidyl methacrylate groups, preferably selected from one or more of styrene-acrylonitrile-glycidyl methacrylate copolymers and ethylene-methyl acrylate-glycidyl methacrylate copolymers;

[0019] In some preferred embodiments, the polyisocyanate compound is selected from one or more of toluene-2,4-diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, lysine diisocyanate and polyisocyanate, preferably polyisocyanate; preferably, the polyisocyanate has a viscosity of 150-250 mPa·s at 25° C., an NCO content of 30.2-32% by weight, and a functionality of 2.6-2.7, such as PM200 of Wanhua Chemical Group Co., Ltd.

[0020] In some embodiments, the raw material optionally further comprises a nucleating agent, and the amount of the nucleating agent is preferably 0-10 parts by weight.

[0021] In some embodiments, the nucleating agent is selected from one or more of talc, silica, mica, and glass fiber.

[0022] Preferably, the extrusion temperature is controlled at 225-240°C;

[0023] Preferably, the feeding section temperature of the twin-screw extruder is 180-210° C., the plasticizing section temperature is 200-230° C., the homogenizing section temperature is 220-235° C., and the extrusion die temperature is 225-235° C. The use of the preferred conditions is conducive to obtaining a film material with better performance.

[0024] The present invention also provides a highly transparent biodegradable film material prepared by the preparation method described above. In some embodiments, the film material obtained by the preparation method of the present invention has a ratio of the melting peak enthalpy to the cold crystallization peak enthalpy of the DSC temperature rise curve of 2:1-8:1, and the crystallinity of the film is less than 30%; the light transmittance of the film is greater than 87%, the haze is less than 10%, and the elongation at break is greater than 260%.

[0025] The present invention also provides application of the above-mentioned highly transparent degradable film material in the field of packaging.

[0026] In the present invention, the modifier terephthalamide is introduced into the formula system of preparing film materials from polyglycolic acid, and is combined with other components in a specific amount. In the process of preparing the film material, the cooling rate is controlled to be ≥150℃ / min (preferably 150-300℃ / min), which can significantly improve the transmittance of the polyglycolic acid film, significantly reduce the haze, and take into account better tensile toughness. In some embodiments, a PGA film with a transmittance greater than 87% and a haze less than 10% is obtained, and the tensile toughness is greatly improved, which broadens the application of PGA materials in the packaging field. DETAILED DESCRIPTION

[0027] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0028] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0029] The present invention will be further described below in conjunction with specific examples. It should be understood that the following examples are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0030] Polyglycolic acid (PGA): Shanghai Pujing Chemical Technology Co., Ltd., weight average molecular weight 150000, melt index 30g / 10min (240℃, 2.16kg);

[0031] Melt compatibilizer: epoxy compound, specifically a copolymer containing glycidyl methacrylate groups, BASF ADR-4468, GMA (glycidyl methacrylate) content of 10% by weight, and a weight average molecular weight of about 6680 g / mol.

[0032] Antioxidant: a compound of a phosphite antioxidant and a hindered phenol antioxidant, specifically antioxidant 168 (tris(2,4-di-tert-butylphenyl)phosphite) and antioxidant 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate) in a 1:1 mass ratio and commercially available.

[0033] Modifier: terephthalamide, purity greater than 98%, commercially available.

[0034] The melt index is measured according to GB / T 3682-2000.

[0035] The crystallinity is calculated according to the formula △Hm / 183.2*100%, wherein △Hm is the endothermic enthalpy value of the DSC curve.

[0036] Crystallization enthalpy ratio: refers to the ratio of the melting peak enthalpy to the cold crystallization peak enthalpy of the DSC heating curve, where the enthalpy value is measured using the DSC program software.

[0037] The light transmittance was measured using the GB / T 2410-2008 method.

[0038] The haze was measured using the GB / T 2410-2008 method.

[0039] The elongation at break is determined using the GB / T 1040.3-2006 method.

[0040] Example 1

[0041] 1. Dry PGA in a vacuum oven for later use. The PGA drying temperature is 80°C and the drying time is 5 hours.

[0042] 2. According to the formula of Table 1, each component is mixed evenly (melt compatibilizer is diphenylmethane diisocyanate), and then the mixed material is put into a twin screw extruder, the feeding section temperature of the twin screw extruder is controlled between 180-210°C, the plasticizing section temperature is controlled between 200-230°C, the homogenizing section temperature is controlled between 220-235°C, and the extrusion die head temperature is controlled between 225-235°C; by melting, extruding and granulating in a twin screw extruder, and then carrying out film pressing, cooling at a cooling rate of 150°C / min to obtain a film material.

[0043] The film obtained by cooling was tested for elongation at break. The results are shown in Table 1.

[0044] The obtained thin film material was subjected to DSC test to obtain the DSC temperature rise curve, and the calculated crystallization enthalpy ratio is shown in Table 1.

[0045] The test results of crystallinity, transmittance and haze of the obtained thin film material are shown in Table 1.

[0046] Example 2

[0047] The same method is carried out with reference to Example 1, except that the amount of each component is changed and the cooling rate is changed. The specific conditions are shown in Table 1. The rest are carried out with reference to Example 1.

[0048] Example 3

[0049] The same method was used as in Example 1, except that the amount of each component and the cooling rate were changed, and the melt compatibilizer used was ADR-4468; the specific conditions are shown in Table 1. The rest of the process was carried out as in Example 1.

[0050] Comparative Example 1

[0051] The same method was used as in Example 1, except that the cooling rate was changed. The specific conditions are shown in Table 1. The rest of the process was carried out as in Example 1.

[0052] Comparative Example 2

[0053] The same method was used as in Example 1, except that the dosage of each component was changed. The specific conditions are shown in Table 1. The rest of the process was carried out as in Example 1.

[0054] Comparative Example 3

[0055] The same method was used as in Example 1, except that the amount of each component and the cooling rate were changed. The specific conditions are shown in Table 1. The rest of the process was carried out as in Example 1.

[0056] Table 1 Ratio (weight) of PGA film materials and performance test results

[0057]

[0058]

[0059] According to the above experimental results, it can be seen that the method of the present invention can be used to produce a film product with better performance based on polyglycolic acid, which can take into account higher light transmittance, lower haze and excellent elongation at break.

[0060] The present invention has been described with reference to the embodiments and examples. However, the present invention is not limited to the aspects described in the above embodiments and examples, and various modifications may be made. However, it should be understood that it is possible for those skilled in the art to make various modifications and equivalent substitutions to the present invention without departing from the spirit and scope of the present invention. Therefore, the present invention is not limited to the specific embodiments described herein. More specifically, the scope of protection of the present invention is defined by the appended claims.

Claims

1. A method for preparing a highly transparent and degradable film material, characterized in that: The following steps are involved: The raw materials are mixed uniformly, and then melt-blended and extruded in a twin-screw extruder to form pellets, and then film pressed and cooled to obtain a film, and during the cooling, the cooling rate is controlled to be ≥150°C / min, preferably 150-300°C / min; The raw materials include the following components: 90-98 parts by weight of polyglycolic acid, 0.3-2 parts by weight of antioxidant, 0.5-3 parts by weight of melt compatibilizer, and 1-5 parts by weight of modifier; The modifier is terephthalamide.

2. The preparation method according to claim 1, characterized in that: The weight average molecular weight of the polyglycolic acid is ≥50,000, preferably 50,000-250,000; the melt index of the polyglycolic acid at 240° C. and 2.16 kg load is 5-120 g / 10 min, preferably 10-50 g / 10 min; The polyglycolic acid is a homopolymer of glycolic acid or a copolymer of glycolic acid.

3. The preparation method according to claim 1, characterized in that: The antioxidant is selected from one or more of phosphite antioxidants and hindered phenol antioxidants, preferably a combination of phosphite antioxidants and hindered phenol antioxidants, preferably with a mass ratio of 0.8-1.2:1; Further preferably, the phosphite antioxidant is selected from one or more of antioxidant 168, antioxidant 626 and antioxidant 9228; the hindered phenol antioxidant is selected from one or more of antioxidant 1010 and antioxidant 1330.

4. The preparation method according to claim 1, characterized in that: The melt compatibilizer is selected from one or more of epoxy compounds and polyisocyanate compounds.

5. The preparation method according to claim 4, characterized in that: The epoxy compound is selected from copolymers containing glycidyl methacrylate groups, preferably selected from one or more of styrene-acrylonitrile-glycidyl methacrylate copolymers and ethylene-methyl acrylate-glycidyl methacrylate copolymers; And / or, the polyisocyanate compound is selected from one or more of toluene-2,4-diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, lysine diisocyanate and polyisocyanate, preferably polyisocyanate; preferably, the polyisocyanate has a viscosity of 150-250 mPa·s at 25° C., an NCO content of 30.2-32% by weight, and a functionality of 2.6-2.

7.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The raw material may further include a nucleating agent, and the amount of the nucleating agent is preferably 0-10 parts by weight.

7. The preparation method according to claim 6, characterized in that: The nucleating agent is selected from one or more of talc, silicon dioxide, mica and glass fiber.

8. The preparation method according to any one of claims 1 to 5, characterized in that: The extrusion temperature is controlled at 225-240°C; Preferably, the feeding section temperature of the twin-screw extruder is 180-210°C, the plasticizing section temperature is 200-230°C, the homogenizing section temperature is 220-235°C, and the extrusion die head temperature is 225-235°C.

9. A highly transparent biodegradable film material prepared by the preparation method according to any one of claims 1 to 8, wherein preferably, the ratio of the melting peak enthalpy to the cold crystallization peak enthalpy of the DSC heating curve of the film material is 2:1-8:1, and the crystallinity of the film is less than 30%; preferably, the transmittance of the film is greater than 87%, the haze is less than 10%, and the elongation at break is greater than 260%.

10. Use of the highly transparent degradable film material according to claim 9 in the field of packaging.

Citation Information

Patent Citations

  • A polylactic acid composite material and its application

    CN108003581B

  • Preparation method of high-transmittance polylactic acid

    CN111440425A

  • Polyglycolic acid material and preparation method and application thereof

    CN112608460A

  • High-crystallinity modified PGA material and preparation method thereof

    CN112679926A

  • Modified polyglycolic acid material and preparation method and application thereof as well as modified polyglycolic acid particles and preparation method and application thereof

    CN115322411A